Virtual Reference Service: ‘Ask Librarian’ Question and Answer (Q&A) Services With Real-Time Systems - Parangu, Reza Nawafella Alya; Yunita, Irva; Parangu, Kaukabilla Alya (UIN Raden Intan Lampung, 2023)
A virtual reference service is a service where librarians and users can communicate with each other in real time over the Internet. This study aims to analyze the virtual reference service 'Ask a Librarian' as a service with a real-time system, which is one of the library strategies for providing reference services to users without limited space and time. This study uses a qualitative approach. This article is based on literature studies that support the subject. The study result shows that the virtual reference service 'Ask a Librarian' makes it easy for reference librarians to provide information on user questions remotely, the quality of the information on this feature is very credible and quality because user questions about any library information are answered directly by the local reference librarian. With the real-time system used in this service, the completion time of activity, responsiveness, or latency is an important aspect of system quality. The presence of these services is expected to provide reference services to users without space constraints in a short time.